Positive electrode active material for lithium secondary battery, manufacturing method thereof, and lithium secondary battery including the same
By introducing lithium layered oxides into the positive electrode active material of lithium-ion secondary batteries and using multivalent metals such as Nb to regulate the growth of main particles to form a single crystal structure, the problem of insufficient rate capability and life characteristics of existing batteries at high temperatures is solved, packaging density and energy density are improved, and the life of the battery is extended.
Patent Information
- Application Number
- JP2025002660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-04-27
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-10-16
AI Technical Summary
The positive electrode active materials of existing lithium-ion secondary batteries have insufficient rate capability and life characteristics at high temperatures, and have low packaging density, resulting in energy density and battery life problems.
By introducing lithium layered oxide (OLO) into the positive electrode active material and using multivalent metals such as Nb as a medium, the growth of main particles is adjusted to form a single crystal structure, thereby improving the stability and energy density of the material.
It improves the packaging density and energy density of the positive electrode active material, reduces the surface area, reduces the electrochemical instability of the battery at high temperatures, and extends the battery life.
Smart Images

Figure 2025061089000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material containing an overlithiated layered oxide (OLO), and more particularly, to a positive electrode active material for a lithium secondary battery in which the size of primary particles is adjusted by a dopant acting as a flux for growing the primary particles, a method for manufacturing the same, and a lithium secondary battery including the same.
Background Art
[0002] With the development of mobile electronic devices such as smartphones, MP3 players, and tablet PCs, the demand for secondary batteries capable of storing electrical energy has been rapidly increasing. In particular, electric vehicles, medium and large-sized energy storage systems, and portable devices requiring high energy density have emerged, and the demand for lithium secondary batteries is increasing.
[0003] In recent years, as a positive electrode active material that has been attracting the most attention, lithium nickel manganese cobalt oxide Li(Ni x Co y Mn 2 )O 2 (wherein x, y, and z are atomic fractions of independent oxide composition elements, respectively, satisfying 0 < x ≤ 1, 0 < y ≤ 1, 0 < z ≤ 1, and 0 < x + y + z ≤ 1). This material has been actively studied and used as a positive electrode active material. Since it is used at a higher voltage than LiCoO 2 , it has the advantage of providing high capacity, and also has the advantage of being low in price because the Co content is relatively small. However, it has the disadvantage that the rate capability and the life characteristics at high temperatures are not sufficient.
[0004] Therefore, the existing Li(Ni x Co y Mn 2 )O 2Research is being conducted to apply overlithiated layered oxide (OLO), which exhibits a high reversible capacity surpassing that of conventional lithium secondary batteries, to lithium secondary batteries.
[0005] However, there is a problem with the voltage decay phenomenon that occurs during the life cycle. This is due to the phase transition from a spinel-like structure to a cubic structure caused by the movement of transition metals during the life cycle. This voltage decay phenomenon is an issue that must be resolved in order to commercialize lithium secondary batteries. In addition, the low packing density is also an issue that needs to be improved. Summary of the Invention [Problem to be solved by the invention]
[0006] The positive electrode active material for a secondary battery including a lithium-excess layered oxide according to an embodiment of the present invention aims to adjust the growth of primary particles to increase the energy density and reduce the specific surface area of the particles compared to conventional polycrystalline OLO.
[0007] Another object of the present invention is to provide a dopant substance for improving the stability of the internal structure of positive electrode active material particles. [Means for solving the problem]
[0008] An overlithiated layered oxide (OLO) according to an embodiment of the present invention is represented by the following [Chemical Formula 1], in which primary particles are aggregated to form secondary particles, and primary particles having a size of 300 nm to 10 μm account for 50 to 100 volume % of all primary particles constituting the secondary particles.
[0009] [C1] JPEG2025061089000002.jpg7159(where 0 < r ≤ 0.6, 0 < a ≤ 1, 0 ≤ x ≤ 1, 0 ≤ y < 1, 0 ≤ z < 1, and 0 < x + y + z < 1, and the said M1 is at least one or more selected from among Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B, and Bi.)
[0010] In the said positive electrode active material according to an embodiment of the present invention, the said primary particles are irregular in shape, and the size of the primary particles means the longest length.
[0011] In the said positive electrode active material according to an embodiment of the present invention, the size of the primary particles in the positive electrode active material state is larger than the size of the primary particles in the precursor state, and the ratio of (the size of the primary particles of the positive electrode active material to which a dopant is added) / (the size of the primary particles of the positive electrode active material to which no dopant is added) is 1 or more, preferably 50 or more.
[0012] In the said positive electrode active material according to an embodiment of the present invention, primary particles having a size of 1 μm to 2 μm may be contained in a content of 50 to 100% by volume with respect to the whole of the said lithium-excess layered oxide.
[0013] Also, the average particle diameter of the said secondary particles of the said positive electrode active material according to an embodiment of the present invention can be 2 μm to 20 μm.
[0014] Also, in the said positive electrode active material according to an embodiment of the present invention, the said M1 in the said [Chemical Formula 1] can be a dopant that acts as a flux for inducing the growth of the said primary particles in the said lithium-excess layered oxide.
[0015] Also, in the said positive electrode active material according to an embodiment of the present invention, the said M1 in the said [Chemical Formula 1] is at least one or more selected from among Nb, Ta, Mo, and W, and the said M1 can be Nb or Ta.
[0016] Further, in the positive electrode active material according to an embodiment of the present invention, the M1 may be contained in an amount of 0.001 to 10 mol% based on the whole of the lithium-excess layered oxide.
[0017] Further, in the positive electrode active material according to an embodiment of the present invention, the M1 is Nb, and the Nb may be contained in an amount of 0.1 to 1 mol% based on the whole of the lithium-excess layered oxide.
[0018] Further, the positive electrode active material according to an embodiment of the present invention is [Chemical Formula 2] Li a M1’O b (wherein 0 < a ≤ 7, 0 < b ≤ 15, and M1’ is at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta, and W).) may be further contained. The Li of [Chemical Formula 2] a M1’O b can be a substance formed by the reaction of a dopant that induces growth between primary particles with lithium.
[0019] Further, with the growth of the primary particles of the positive electrode active material according to an embodiment of the present invention, during XRD analysis, the full width at half maximum (FWHM (deg.)) at I(104) can be reduced by 5 to 50% by including M1 compared to a substance not containing M1 when fired under the same conditions.
[0020] Further, the energy density (Wh / L) per volume of the positive electrode active material according to an embodiment of the present invention can be 2.7 to 4.0 (Wh / L).
[0021] Further, the energy density (Wh / L) per volume of the positive electrode active material according to an embodiment of the present invention can be increased by 5 to 30% compared to a substance not containing M1.
[0022] Further, the packing density (g / cc) of the positive electrode active material according to an embodiment of the present invention can be 2.0 to 4.0 (g / cc).
[0023] In addition, the specific surface area (BET, m 2 / g) is 0.1 to 1.5 (BET, m 2 / g).
[0024] In addition, the specific surface area (BET, m 2 / g) can decrease by 25-80% relative to materials not containing M1 as the primary particles grow.
[0025] In the positive electrode active material according to the embodiment of the present invention, the ratio of the number of moles of lithium to the total number of moles of a metal selected from Ni, Co, or Mn (Li / (Ni+Co+Mn)) may be 1.1 to 1.6.
[0026] In the positive electrode active material according to the embodiment of the present invention, the ratio of the number of moles of Mn to the total number of moles of Ni (Mn / Ni) can be 1 to 4.5.
[0027] In addition, the positive electrode active material according to the embodiment of the present invention is a monoclinic structure Li 2 MnO 3 and LiMO, which has a rhombohedral structure. 2 and M may be at least one selected from the group consisting of Ni, Co, Mn, and M1.
[0028] In addition, the positive electrode active material according to the embodiment of the present invention has a Li 2 MnO 3 It is possible to show a plateau due to the
[0029] The method for producing the positive electrode active material according to the embodiment of the present invention includes the steps of: producing a positive electrode active material precursor containing at least one element selected from Ni, Co, and Mn; and mixing the positive electrode active material precursor with a lithium compound and a compound containing M1 in [Chemical Formula 1], and firing the mixture.
[0030] In the method for producing the positive electrode active material according to the embodiment of the present invention, the size of the primary particles in the positive electrode active material state is larger than the size of the primary particles in the precursor state, and the ratio of (the size of the primary particles of the positive electrode active material with added dopant) / (the size of the primary particles of the positive electrode active material without added dopant) is 1 or more, preferably 50 or more.
[0031] In the method for producing a positive electrode active material according to the embodiment of the present invention, the temperature of the firing step may be 750 to 950°C.
[0032] In addition, the method for preparing a positive electrode active material according to an embodiment of the present invention may further include a step of roasting the obtained precursor after the step of preparing the precursor and before the step of firing, and a temperature of the roasting step may be 300 to 600°C.
[0033] In the method for producing a positive electrode active material according to the embodiment of the present invention, the M1 is Nb, and the compound containing Nb is Nb 2 O 5 It is characterized in that:
[0034] In addition, the method for preparing a positive electrode active material according to an embodiment of the present invention may further include, after the calcination step, washing and drying the calcined positive electrode active material.
[0035] In addition, the method for manufacturing a positive electrode active material according to an embodiment of the present invention may further include, after the calcination step, a step of heat-treating the calcined positive electrode active material.
[0036] A secondary battery according to an embodiment of the present invention includes the positive electrode active material. Effect of the Invention
[0037] The lithium-excess layered oxide-containing positive electrode active material for secondary batteries according to the embodiment of the present invention contains a dopant material for improving the stability of the internal structure of the positive electrode active material particles, and thus the primary particles are single-crystallized, thereby improving the packing density, improving the energy density, and reducing the specific surface area of the particles, compared to the conventionally known polycrystalline lithium-excess positive electrode active material (OLO).
[0038] In addition, the secondary battery including the positive electrode active material has a reduced specific surface area and thus a reduced surface area of the positive electrode active material, compared to a battery using a conventionally known polycrystalline lithium-excess positive electrode active material (OLO), and therefore the problems of life span and voltage drop are significantly reduced. [Brief description of the drawings]
[0039] [Figure 1] 1 is a SEM analysis image of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 2A] 2a and 2b are SEM analysis images of cross sections of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 2B] 2a and 2b are SEM analysis images of cross sections of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 3A] 3a and 3b are diagrams showing the results of EDX analysis of the positive electrode active materials according to the comparative example and the example of the present invention. [Figure 3B] 3a and 3b are diagrams showing the results of EDX analysis of the positive electrode active materials according to the comparative example and the example of the present invention. [Figure 4] FIG. 2 is a diagram showing the results of XRD analysis of positive electrode active materials according to comparative examples and examples of the present invention. [Diagram 5] FIG. 2 is a diagram showing the results of XRD analysis of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 6]1 is a graph comparing the measurement results of X-ray diffraction (XRD) analysis and the full width at half maximum (FWHM (deg.)) at I(104) of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 7] 1 is a graph comparing packing density (g / cc) of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 8] 1 is a graph comparing the specific surface area (BET, m2 / g) of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 9] 1 is a graph comparing initial voltage profiles of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 10] 1 is a graph comparing the energy density per volume of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 11] 1 is a graph comparing capacity retention according to cycle number of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 12] 1 is a graph comparing the capacity according to the cycle number of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 13] 1 is a graph comparing voltage retention according to cycle number of positive electrode active materials according to comparative examples and examples of the present invention. [Figure 14] 1 is a graph comparing nominal voltage according to cycle number of positive electrode active materials according to comparative examples and examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] The term "comprising" as used herein should be understood as an open-ended term that encompasses the possibility of including other embodiments.
[0041] As used herein, the terms "preferred" and "preferably" refer to embodiments of the invention that may provide certain advantages, under certain circumstances, and do not exclude other embodiments from the scope of the invention.
[0042] Hereinafter, a cathode active material according to an embodiment of the present invention will be described in detail.
[0043] The positive electrode active material according to the embodiment of the present invention includes an overlithiated layered oxide (OLO).
[0044] The lithium-rich layered oxide is a monoclinic structure Li 2 MnO 3 and LiMO, which has a rhombohedral structure. 2 and M may be at least one selected from the group consisting of Ni, Co, Mn, and M1.
[0045] In addition, the excess layered oxide according to the embodiment of the present invention has a Li 2 MnO 3 The lithium-excess layered oxide according to the embodiment of the present invention has a plateau due to Li up to a region of 4.4 V against lithium during the initial charge process. 2 MnO 3 The Li phase is electrochemically inactive and at 4.4 V or higher, 2 MnO 3 Lithium desorption from the phase and oxygen evolution can occur.
[0046] The lithium-excess layered oxide according to the embodiment of the present invention is represented by the following formula (1). [C1] JPEG2025061089000003.jpg496(where 0 < r ≤ 0.6, 0 < a ≤ 1, 0 ≤ x ≤ 1, 0 ≤ y < 1, 0 ≤ z < 1, and 0 < x + y + z < 1, and M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B, and Bi.)
[0047] The molar percentage ratio of lithium (Li / (Ni + Co + Mn)) can be 1.1 to 1.6 with respect to the total number of moles of the metal selected from Ni, Co, or Mn.
[0048] In the lithium-excess layered oxide represented by [Chemical Formula 1], the molar ratio of lithium (Li / (Ni + Co + Mn)) can be 1.1 to 1.6, 1.2 to 1.6, 1.2 to 1.5, 1.2 to 1.4, or 1.2 to 1.3 with respect to the total number of moles of the metal selected from Ni, Co, or Mn.
[0049] In [Chemical Formula 1], the value of x can be greater than 0 to 0.5, greater than 0 to 0.4, greater than 0 to 0.3, greater than 0 to 0.2, or greater than 0 to 0.1.
[0050] In [Chemical Formula 1], the value of y can be greater than 0 to 0.5, greater than 0 to 0.4, greater than 0 to 0.3, greater than 0 to 0.2, or greater than 0 to 0.1.
[0051] Also, the molar ratio of Mn to Ni (Mn / Ni) can be 1 to 4.5, 1 to 4, 2 to 4.5, 2 to 4, 3 to 4.5, or 3 to 4 with respect to the total number of moles of Ni.
[0052] The positive electrode active material according to the present invention is an oxide rich in lithium and manganese, and by adjusting the ratio of the contents of Mn and Li to the grain boundary density within a predetermined range, problems such as density and voltage drop can be efficiently improved.
[0053] The oxide of the present invention can have a layered structure in which lithium atomic layers and metal atomic layers of Ni, Co, Mn, or M1 are alternately stacked with oxygen atomic layers interposed therebetween.
[0054] The planes constituting the layers of the layered structure of the positive electrode active material can have a crystal orientation in a direction perpendicular to the C-axis. In this case, the mobility of lithium ions contained in the positive electrode active material is improved, and the structural stability of the positive electrode active material is increased, so that when the positive electrode active material is applied to a battery, the initial capacity characteristics, output characteristics, resistance characteristics, and long life characteristics can be improved.
[0055] In addition, for example, the positive electrode active material including the lithium-excess layered oxide according to the present invention may have a single-crystal structure.
[0056] In the positive electrode active material according to the embodiment of the present invention, primary particles may be aggregated to form secondary particles, and the size of the primary particles may be 0.01 to 10 μm.
[0057] In addition, in the positive electrode active material according to the embodiment of the present invention, the primary particles having a size of 300 nm to 5 μm may be adjusted to 50 to 100 volume %, 70 to 100 volume %, or 100 volume % of all the primary particles constituting the secondary particles.
[0058] In addition, in the positive electrode active material according to the embodiment of the present invention, the primary particles having a size of 300 nm to 10 μm may be adjusted to 50 to 100 volume %, 70 to 100 volume %, or 100 volume % of all the primary particles constituting the secondary particles.
[0059] Also, as an example, the positive electrode active material may be adjusted so that primary particles having a size of more than 500 nm to 10 μm account for 50 to 100 volume %, 70 to 100 volume %, or 100 volume % of all primary particles constituting the secondary particles.
[0060] As an example, the positive electrode active material may contain primary particles having a size of 1 μm to 2 μm in a content of 50 to 100% relative to the total amount of primary particles constituting the secondary particles.
[0061] As an example, the positive electrode active material may have primary particles having a size of 1 μm to 10 μm adjusted to 50 to 100 vol%, 70 to 100 vol%, or 100 vol% based on the entire lithium-excess layered oxide.
[0062] As an example, the positive electrode active material may have primary particles having a size of more than 1 μm adjusted to 50 to 100 vol%, 70 to 100 vol%, or 100 vol% based on the entire lithium-excess layered oxide.
[0063] As an example, the positive electrode active material may have primary particles having a size of 2 μm or more adjusted to 50 to 100% by volume, or less than 50 to 70% by volume, based on the entire lithium-excess layered oxide.
[0064] The primary particle size means the longest length of the particle.
[0065] As an example, the average particle size of the primary particles of the positive electrode active material may be adjusted to be greater than 500 nm and 10 μm, or 1 μm to 10 μm.
[0066] In the present invention, the average particle size is defined as a particle size corresponding to 50% of the cumulative volume in a particle size distribution curve. The average particle size can be measured, for example, by a laser diffraction method.
[0067] In the present invention, the size of the primary particles in the lithium-excess layered oxide is increased to adjust the oxide to have a single crystal structure, and thus when calcined under the same conditions, the half-width (FWHM (deg.)) at I(104) in XRD analysis can be adjusted so that when M1 is contained, the full width at half maximum (FWHM (deg.)) at I(104) is reduced by 5 to 25%, 5 to 20%, 10 to 25%, or 10 to 20% compared to a comparative example not containing M1.
[0068] In addition, in the positive electrode active material according to the present invention, the size of the primary particles in the lithium-excess layered oxide is increased to adjust the material to have a single crystal structure, and thus the energy density per volume (Wh / L) can be adjusted to increase by 5 to 25%, 5 to 20%, 10 to 25%, or 10 to 20% when M1 is contained, compared to a comparative example not containing M1.
[0069] In addition, the positive electrode active material according to the present invention has a specific surface area (BET, m 2 / g) can be adjusted to be reduced by 20 to 80% when M1 is contained, compared to a comparative example not containing M1.
[0070] Conventionally, lithium-rich layered oxides have a problem of voltage drop during cycling. The voltage drop is caused by a phase transition from a structure similar to a spinel to a cubic structure due to the movement of transition metals during cycling, and this phenomenon occurs mainly at the surface of the positive electrode active material. The present invention induces the growth of the primary particles and adjusts the positive electrode active material to have a single crystal, thereby increasing the energy density per volume, decreasing the specific surface area, and reducing the surface area of the positive electrode active material, thereby solving the problems of lifespan and voltage drop. In the present invention, the induction of growth of the primary particles includes all of the concepts of nucleation, ostwald ripening, and particle aggregation.
[0071] Furthermore, the reduction in the specific surface area makes it possible to solve the problem of side reactions occurring with the electrolyte.
[0072] In the positive electrode active material according to the present invention, the greater the portion corresponding to the single crystal structure, the more the problem of voltage drop occurring in polycrystals can be improved.
[0073] The positive electrode active material according to the present invention includes M1 in [Chemical Formula 1] as a dopant that induces growth between primary particles. More preferably, M1 is a dopant that acts as a flux that induces growth between primary particles in the lithium-excess layered oxide, and can be doped into the lattice structure. As an example, the flux dopant can be added and mixed in the firing step with the lithium compound, and then heat treated together to adjust the size of the primary particles to increase. Acting as a flux means that it can act as a dopant that increases the size of the primary particles by the growth between the primary particles.
[0074] The M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B, and Bi, more preferably at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta, and W, which can grow the size of the primary particles and more appropriately adjust it to a specific range, and most preferably at least one selected from Nb and Ta.
[0075] In the positive electrode active material according to the present invention, when a dopant element that induces growth between the primary particles is mixed with a lithium compound in a firing step and then heat-treated together, the surface area of the positive electrode active material is reduced, thereby improving problems of lifespan and voltage drop.
[0076] The cathode active material according to the present invention is such that the dopant element is uniformly contained in the surface and inside of the cathode active material, whereby the structural stability of the cathode active material is improved, and the life characteristics and thermal stability can be improved.
[0077] In the cathode active material according to the present invention, M1 can be contained in an amount of 0.01 to 3 mol% based on the entire amount of the lithium-excess layered oxide. Further, it can be contained in an amount of 0.1 to 2 mol%, more preferably 0.1 to 1 mol%. When the dopant M1 contained as a flux for inducing the growth of primary particles exceeds the above range, the lithium composite oxide becomes excessive and causes a decrease in capacity and efficiency. When it is less than the above range, the effect of growing primary particles cannot be sufficiently obtained.
[0078] Further, the cathode active material for a secondary battery according to an embodiment of the present invention may further contain a lithium-excess layered oxide (overlithiated layered oxide: OLO) represented by the following [Chemical Formula 2]. [Chemical Formula 2] JPEG2025061089000004.jpg12159(wherein 0 < a ≤ 7, 0 < b ≤ 15, and M1' is at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta, and W).)
[0079] Li in the above [Chemical Formula 2] a M1'O b can be a substance generated by the reaction of a dopant that induces the growth between primary particles with lithium.
[0080] When performing XRD analysis of the cathode active material according to an embodiment of the present invention, the full width at half maximum (FWHM (deg.)) at I(104) can be 0.1 to 2.45 (deg.), but the value can vary depending on the manganese content. Therefore, by adjusting the addition and content of the dopant M1 to adjust the reduction rate of the full width at half maximum, problems of life and voltage drop can be solved.
[0081] In addition, the energy density per volume (Wh / L) of the positive active material according to an embodiment obtained by adjusting the addition and content of the dopant M1 may be 2.7 to 4.0 (Wh / L).
[0082] In addition, the specific surface area (BET, m 2 / g) is 0.01 to 2 (BET, m 2 / g).
[0083] The average particle size of the positive electrode active material particles according to the embodiment of the present invention may be 0.1 to 30 μm, or 0.1 to 25 μm, or 0.1 to 20 μm, or 0.1 to 15 μm, or 0.1 to 10 μm.
[0084] The positive electrode active material including the lithium-excess layered oxide according to the embodiment of the present invention may have a structure in which primary particles grow to form secondary particles.
[0085] The particle form of the positive electrode active material may be fibrous, membrane, or spherical, and is more preferably spherical.
[0086] In the present invention, the average particle size is defined as the particle size corresponding to 0% of the cumulative volume in the particle size distribution curve. The average particle size can be measured, for example, by using a laser diffraction method.
[0087] The shape of the primary particles may be rod-like, plate-like, spherical, elliptical, disk-like, or irregular. Preferably, the shape of the primary particles is at least one of a plate-like shape and an irregular shape.
[0088] In the positive electrode active material according to the embodiment of the present invention, the number of the primary particles in the secondary particles can be adjusted to 1 to 10,000, 1 to 1,000, 1 to 100, or 1 to 10 by adjusting the size of the primary particles.
[0089] The positive electrode active material according to the embodiment of the present invention may further include a coating layer.
[0090] The coating layer may include one or more coating materials selected from the group consisting of P, Nb, Si, Sn, Al, Pr, Al, Ti, Zr, Fe, Al, Fe, Co, Ca, Mn, Ti, Sm, Zr, Fe, La, Ce, Pr, Mg, Bi, Li, W, Co, Zr, B, Ba, F, K, Na, V, Ge, Ga, As, Sr, Y, Ta, Cr, Mo, W, Mn, Ir, Ni, Zn, In, Na, K, Rb, Cs, Fr, Sc, Cu, Ru, Rh, Pd, Ag, Cd, Sb, Hf, Ta, Re, Os, Pt, Au, Pb, Bi, and Po, but is not limited thereto.
[0091] The coating layer blocks contact between the positive electrode active material and the electrolyte contained in the lithium secondary battery to suppress the occurrence of side reactions, thereby improving the life characteristics and increasing the packing density, and the coating layer enables the positive electrode active material to act as a lithium ion conductor.
[0092] In addition, the coating layer may be formed between grain boundaries of the primary particles.
[0093] The coating layer may have a thickness of 0.1 to 500 nm. The coating layer may be formed on the entire surface of the positive electrode active material or on a part of the surface.
[0094] The coating layer may be in the form of a single layer coating, a double layer coating, a grain boundary coating, a uniform coating, or an island coating.
[0095] In the positive electrode active material including the lithium-excess layered oxide according to the embodiment of the present invention, the positive electrode active material may include a concentration gradient portion in which at least one of the Ni, Co, Mn, and M1 exhibits a concentration gradient in at least a part of the inside and outside of the positive electrode active material particle, i.e., the inside and outside of the secondary particle or the inside and outside of the primary particle.
[0096] In the positive electrode active material according to the embodiment of the present invention, a lithium ion diffusion path may be provided within the primary particles.
[0097] In the positive electrode active material according to the embodiment of the present invention, the surfaces constituting the layers of the layered structure have a crystal orientation in a direction perpendicular to the C-axis within the primary particles, and a lithium ion migration path can be provided toward the center of the positive electrode active material particle inside or outside the primary particles.
[0098] Hereinafter, a method for manufacturing a positive electrode active material according to an embodiment of the present invention will be described in detail.
[0099] The method for manufacturing a positive electrode active material for a secondary battery according to the embodiment of the present invention includes a step of manufacturing a precursor of a positive electrode active material containing at least one element selected from the group consisting of Ni, Co, and Mn.
[0100] To produce the precursor, as raw materials for nickel, cobalt, manganese, and dopants, sulfates, nitrates, acetates, halides, hydroxides, oxyhydroxides, etc. containing the respective metal elements can be used, and there are no particular limitations on the types of raw materials that can be used as long as they are soluble in a solvent such as water.
[0101] The precursor can be prepared by co-precipitation, spray-drying, solid phase method, wet grinding, fluidized bed drying, vibration drying, and the like.
[0102] In the method for producing the positive electrode active material for secondary batteries according to the embodiment of the present invention, a lithium compound and a compound containing M1 in [Chemical Formula 1], which is a dopant contained as a flux for inducing growth between primary particles, are mixed with the obtained precursor of the positive electrode active material, and then calcined.
[0103] In the present invention, the dopant M1, which is included as a flux that induces growth between primary particles in the firing step with the lithium compound, is added as a flux dopant to grow the primary particles and reduce the surface area of the positive electrode active material, thereby making it possible to solve the problems of life span and voltage drop.
[0104] In the method for producing a positive electrode active material for a secondary battery according to the present invention, the lithium compound may be, but is not limited to, a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide.
[0105] The temperature of the firing step can be 750 to 950°C, 800 to 950°C, or 850 to 950°C.
[0106] In addition, the method may further include a step of roasting the obtained precursor after the precursor preparation step and before the firing step described below, and the temperature of the roasting step may be 300 to 600°C, 400 to 600°C, or 500 to 600°C.
[0107] The step of roasting the precursor may be performed by repeatedly increasing the temperature and maintaining the temperature, or by increasing the temperature, maintaining the temperature, cooling, increasing the temperature again, maintaining the temperature, and cooling in that order.
[0108] In addition, the method may further include washing and drying the fired positive electrode active material after the firing step.
[0109] Furthermore, after performing the above steps, a step of forming a coating layer on the inside or outside of the positive electrode active material may be included, and the coating layer may be formed by a dry coating, wet coating, CVD coating, or ALD coating method. However, the coating method is not limited thereto as long as it is possible to form a coating layer on a part of the positive electrode active material.
[0110] Any of the above descriptions regarding the positive electrode active material can be applied to the method for producing the positive electrode active material.
[0111] The secondary battery according to the embodiment of the present invention includes the above-mentioned positive electrode active material.
[0112] The positive electrode active material is as described above, and the binder, conductive material, and solvent are not particularly limited as long as they can be used on the positive electrode current collector of a secondary battery.
[0113] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but is not particularly limited as long as it can be used as a secondary battery.
[0114] The present invention will be described in detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0115] <Example 1> Preparation of positive electrode active material synthesis Using the co-precipitation method, spherical Ni 0.2 Co 0.1 Mn 0.7 CO 3 The precursor was synthesized.
[0116] In a 90L reactor, NiSO 4 6H 2 O, CoSO 4 7H 2 O, and MnSO 4 H 2O was mixed in a molar ratio of 20:10:70 to a 2.5M aqueous solution of composite transition metal sulfate, and 25wt% NaCO 3 and 28 wt% NH 4 At this time, the pH in the reactor was maintained at 8.0 to 11.0, and the temperature was maintained at 45 to 50°C. In addition, in order to prevent the obtained precursor from being oxidized, an inert gas, N 2 After the synthesis and mixing was completed, the mixture was washed and dehydrated using a filter press (F / P). Finally, the dehydrated product was dried at 120°C for 2 days and sieved through a 75μm (200mesh) sieve to separate 4~20μm Ni particles. 0.2 Co 0.1 Mn 0.7 CO 3 The precursor of
[0117] Roasting The obtained precursor is heated in a box furnace. 2 Alternatively, while maintaining an atmosphere of air (50 L / min), the temperature was increased at 2° C. / min, and after maintaining at 550° C. for 1 to 6 hours, furnace cooling was performed.
[0118] Firing The calcined precursor was treated with LiOH or Li to obtain a Li / (Ni+Co+Mn) ratio of 1.45. 2 CO 3 was weighed, and Nb was used as a flux dopant to induce growth between primary particles. 2 O 5 was weighed out in an amount of 0.3 mol % and mixed using a mixer (Manual mixer: MM).
[0119] The mixture is baked in a box furnace. 2 Alternatively, while maintaining an air (50 L / min) atmosphere, the temperature was increased at 2° C. / min, and the firing temperature was maintained at 900° C. for 7 to 12 hours, followed by furnace cooling to produce a positive electrode active material.
[0120] The composition of the positive electrode active material produced in Example 1 was Li:Ni:Co:Mn:Nb=15.3:15.1:9.3:59.8:0.4 (wt %).
[0121] <Example 2> Preparation of positive electrode active material In the firing step of Example 1 above, Nb was used as a flux dopant. 2 O 5 A positive electrode active material was produced in the same manner as in Example 1, except that 0.6 mol % of was mixed.
[0122] The composition of the positive electrode active material produced in Example 2 was Li:Ni:Co:Mn:Nb=15.0:14.8:9.3:60.0:0.8 (wt %).
[0123] <Comparative Example 1> Preparation of Positive Electrode Active Material In the firing step of Example 1 above, Nb was used as a flux dopant. 2 O 5 A positive electrode active material was produced in the same manner as in Example 1, except that the was not mixed.
[0124] <Comparative Example 2> Preparation of Positive Electrode Active Material Ammonium niobate oxalate (C 2 O 4 ) was used as the flux dopant in the calcination step of Example 2 above. 4 H 4 NNbO 9 xH 2 A positive electrode active material was produced in the same manner as in Example 2, except that the above-mentioned component (I) was mixed.
[0125] <Experimental Example> SEM Measurement The positive electrode active materials produced in the above-mentioned Examples and Comparative Examples were subjected to SEM measurement, and the results are shown in FIG.
[0126] As shown in the figure, the size of the primary particles of the positive electrode active material according to Example 1 is larger than that of the comparative example, and the Nb 2 O 5 It was confirmed that the larger the amount of added, the larger the primary particle size.
[0127] In the case of the cathode active material prepared according to the embodiment of the present invention, the size of the primary particles was measured to be 300 nm to 5 μm, and it was confirmed that the size of the primary particles can be adjusted to sub-micron size, instead of the conventional nano-sized primary particles.
[0128] In Comparative Example 2, the Nb compound was also added at 0.6 mol %, but unlike the Nb compound used in Comparative Example 1, it was confirmed that the particle size was smaller than that of Example 1, in which a smaller amount of Nb was added at 0.3 mol %.
[0129] <Experimental Example> Cross-Sectional SEM Measurement Cross-sectional SEM images of the positive electrode active materials prepared in the above examples and comparative examples were taken, and the results are shown in FIGS. 2a and 2b.
[0130] FIG. 2a is a cross-sectional SEM image of the cathode active material prepared in Comparative Example 1. It was confirmed that not only the primary particles present outside the secondary particles of the cathode active material but also the primary particles present inside the secondary particles were small in size.
[0131] FIG. 2b is a cross-sectional SEM image of the cathode active material prepared in Example 2, which shows that not only the primary particles present outside the secondary particles of the cathode active material but also the primary particles present inside the secondary particles have grown in size.
[0132] <Experimental Example> EDX Measurement The positive electrode active materials prepared in the above examples and comparative examples were photographed using EDX, and the results are shown in FIGS. 3a and 3b.
[0133] FIG. 3a shows the EDX result of the positive electrode active material to which the flux dopant prepared in Example 2 was added. It was confirmed that not only the elements Ni, Co, and Mn, but also Nb, which was added as a flux dopant to induce growth between primary particles, was uniformly contained within the particles.
[0134] FIG. 3b shows the EDX result of the positive electrode active material prepared in Comparative Example 1 above, to which no flux dopant was added, and it was confirmed that only the elements Ni, Co, and Mn were uniformly contained within the particles.
[0135] <Experimental Example> XRD Analysis The results of XRD analysis of the positive electrode active materials produced in the examples of the present invention and the comparative examples are shown in Figures 4 to 6. The XRD analysis was performed using CuKα radiation at a wavelength of 1.5406 Å.
[0136] From Figure 4, it was confirmed that when a flux dopant was added, the major peak I(003) of the lithium-rich layered oxide shifted to a lower angle during XRD analysis, which was confirmed to be evidence that the flux dopant Nb was doped into the lattice of the lithium-rich layered oxide.
[0137] From FIG. 5, when Nb is mixed according to Example 2 of the present invention, Li 3 NbO 4 It was confirmed that a peak due to
[0138] From FIG. 6, it was confirmed that in the XRD analysis of the positive electrode active material according to the above-mentioned embodiment, the full width at half maximum (FWHM (deg.)) at I(104) was reduced compared to the comparative example, and the full width at half maximum was reduced as the content of the flux dopant inducing the growth between primary particles was increased.
[0139] More specifically, it was confirmed that the reduction rate was adjusted to 7.5% by adding 0.3 mol% Nb as a flux dopant that induces growth between primary particles, and that the reduction rate was adjusted to 17.3% by adding 0.6 mol% Nb. Even though the firing temperature was the same, it was confirmed that the size of the primary particles could be adjusted by adding a dopant, and thus the half-width at I(104) could be adjusted.
[0140] <Experimental Example> Packing density measurement From FIG. 7, it was confirmed that the packing density (g / cc) of the positive electrode active material according to the above-mentioned embodiment is increased compared to the above-mentioned comparative example, and the packing density increases as the content of the flux dopant increases.
[0141] <Experimental Example> BET Measurement From FIG. 8, the specific surface area (BET, m 2 / g) decreased compared to the comparative example, and the specific surface area (BET, m 2 More specifically, it was confirmed that the specific surface area was reduced by 60% when 0.3 mol% of Nb was added as a flux dopant, and the specific surface area was reduced by more than 80% when 0.6 mol% was added.
[0142] <Experimental Example> Electrochemical property measurement 9, it was confirmed that the embodiment in which the flux dopant that induces the growth of primary particles was added in the sintering step had superior voltage characteristics compared to the comparative example in which the flux dopant was not added. As such, the initial charge / discharge capacity of the positive electrode active material containing the lithium-excess layered oxide is increased compared to the comparative example because the flux dopant increases inter-slabs and the ion conductor coating layer increases the kinetics of lithium ions (Li ions).
[0143] 10, it was confirmed that the energy density per volume (Wh / L) of the positive electrode active material according to the above-mentioned embodiment is increased as the content of the flux dopant is increased compared to that of the comparative example. More specifically, it was confirmed that the energy density per volume (Wh / L) was adjusted to 9.1% by adding 0.3 mol% of Nb as the flux dopant, and the energy density per volume (Wh / L) was adjusted to 14.9% by adding 0.6 mol% of Nb as the flux dopant.
[0144] From FIG. 11, it was confirmed that the embodiment in which the flux dopant was added in the firing step had superior voltage characteristics compared to the comparative example in which the flux dopant was not added, and that the capacity retention as a function of the cycle number was maintained as the content of the flux dopant was increased.
[0145] From FIG. 12, it was confirmed that the embodiment in which the flux dopant was added in the firing step had superior voltage characteristics compared to the comparative example in which the flux dopant was not added, and that the capacity was maintained according to the cycle number as the content of the flux dopant was increased.
[0146] From FIG. 13, it was confirmed that the embodiment in which the flux dopant was added in the firing step had superior voltage characteristics compared to the comparative example in which the flux dopant was not added, and that the voltage retention as a function of the cycle number was maintained as the flux dopant content was increased.
[0147] From FIG. 14, it can be seen that the embodiment in which the flux dopant was added in the firing step had superior voltage characteristics compared to the comparative example in which the flux dopant was not added, and that the nominal voltage was maintained according to the cycle number as the flux dopant content was increased.
[0148] The results of the above experiments are shown in Table 1 below. [Table 1]
Claims
1. A positive electrode active material comprising an overlithiated layered oxide (OLO) represented by the following [Chemical Formula 1]: The M1 in the [Chemical Formula 1] is contained in an amount of 0.3 to 10 mol % based on the total number of moles of the metals constituting the positive electrode active material, The positive electrode active material further contains a substance represented by the following [Chemical Formula 2]: Positive electrode active material for secondary batteries. [Chemical formula 1] (In the formula, 0<r≦0.6, 0<a≦1, 0≦x≦1, 0≦y<1, 0≦z<1, and 0<x+y+z<1, and M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B, and Bi.) [Case 2] (In the formula, 0<a≦7, 0<b≦15, and M1′ is at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Ta, and W.)
2. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the average particle size of the secondary particles of the positive electrode active material is 2 μm to 20 μm.
3. 2. The positive electrode active material for a secondary battery according to claim 1, wherein M1 in the formula 1 is a dopant that acts as a flux for growing primary particles.
4. 2. The positive electrode active material for a secondary battery according to claim 1, wherein the packing density of the positive electrode active material is 2.0 to 4.0 (g / cc).
5. The specific surface area (BET, m 2 / g) is 0.1 to 1.5 (BET, m 2 2. The positive electrode active material for a secondary battery according to claim 1, wherein the molecular weight of the positive electrode active material is 1.0 / g.
6. 2. The positive electrode active material for a secondary battery according to claim 1, wherein in the lithium-excess layered oxide, a ratio of the number of moles of lithium to the total number of moles of Ni, Co, or Mn metal (Li / (Ni+Co+Mn)) is 1.1 to 1.
6.
7. 2. The positive electrode active material for a secondary battery according to claim 1, wherein in the lithium-excess layered oxide, a ratio of the number of moles of Mn to the total number of moles of Ni (Mn / Ni) is 1 to 4.
5.
8. A step of producing a positive electrode active material precursor containing at least one element selected from Ni, Co, and Mn; and a step of mixing the positive electrode active material precursor with a lithium compound and a compound containing M1 in the [Chemical Formula 1], and calcining the mixture; The method for producing a positive electrode active material for a secondary battery according to claim 1 , comprising:
9. 9. The method of claim 8, further comprising the step of roasting the prepared precursor at 300 to 600 ° C. after the step of preparing the precursor and before the step of calcining.
10. A secondary battery comprising the positive electrode active material according to claim 1.
Citation Information
Patent Citations
Cathode active material for nonaqueous secondary battery, and nonaqueous secondary battery using the same
JP2013073826A
Positive electrode active material comprising lithium-rich lithium manganese oxide and a lithium tungsten compound on the lithium-rich lithium manganese oxide, or a tungsten compound in addition, and positive electrode for lithium secondary battery including the same
JP2020511741A
Positive active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same
KR1020130058590A